الإطناب : ذكر الخاص بعد العام وبالعكس، والإيضاح بعد العام والتكرار، والاعتراض في القرآن - Fatimah Azzahra Putri; Hidayat Hidayat; Zainal Muttaqin (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2026)
This paper explores the rhetorical concept of al-Iṭnâb (overstatement) in the Qur’an, a significant stylistic feature within the field of Arabic rhetoric (balāghah). Al-Iṭnâb is discussed as a linguistic strategy that involves extending expressions without altering their core meaning, enhancing clarity, emphasis, and aesthetic appeal. Specifically, the study examines four primary forms of al-Iṭnâb found in the Qur’anic text: (1) the specification of a general statement with a particular one, (2) the explanation following a general statement, (3) repetition, and (4) interruption or interjection within sentences. Using a qualitative descriptive approach, this study analyzes Qur’anic verses that illustrate these forms, employing content analysis based on classical balāghah theories. The findings demonstrate that al-Iṭnâb is not merely an embellishment but serves profound communicative purposes: reinforcing meanings, emphasizing divine messages, and beautifying the language. The research underscores the importance of understanding the Qur’anic rhetorical system for interpreting its deeper spiritual and aesthetic meanings.